Evaluation of Perovskites as Electrocatalysts for the Oxygen Evolution Reaction. Issue 13 (13th July 2014) - Rincón, Rosalba A.; Ventosa, Edgar; Tietz, Frank; Masa, Justus; Seisel, Sabine; Kuznetsov, Volodymyr; Schuhmann, Wolfgang
Abstract The oxygen evolution reaction (OER) is an enabling process for technologies in the area of energy conversion and storage, but its slow kinetics limits its efficiency. We performed an electrochemical evaluation of 14 different perovskites of variable composition and stoichiometry as OER electrocatalysts in alkaline media. We particularly focused on improved methods for a reliable comparison of catalyst activity. From initial electrochemical results we selected the most active samples for further optimization of electrode preparation and testing. An inverted cell configuration facilitated gas bubble detachment and thus minimized blockage of the active surface area. We describe parameters, such as the presence of specific cations, stoichiometry, and conductivity, that are important for obtaining electroactive perovskites for OER. Conductive additives enhanced the current and decreased the apparent overpotential of OER for one of the most active samples (La0.58Sr0.4Fe0.8Co0.2O3).